Damage assessment of reinforced concrete beams using cost-effective MEMS accelerometers. (July 2022) - Khan, Sultani Mulk; Hanif, Muhammad Usman; Khan, Azam; Hassan, Muhammad Usman; Javanmardi, Ahad; Ahmad, Atif
Abstract: Acquisition of vibration data using off-the-shelf equipment is a costly procedure, thus constraining the research and development in developing countries. In this research, micro-electromechanical systems (MEMS) accelerometers combined with an Arduino-based data acquisition system, were used to acquire vibration data of a reinforced concrete beam at various damage levels. The recorded data, having lower and varying sampling frequency, were processed to find the fundamental frequency of the beam. The results showed good agreement with the commercially available accelerometers. To integrate the experimental and computational work, a finite element model was developed which showed good agreement with the experiment. It was found that MEMS accelerometers are cost-effective and can be effectively employed for continuous health monitoring of existing civil infrastructure.